LITERATURE REVIEW OF TYPES AND RELATIONS OF WORD MEANINGS AT THE LINGUISTIC LEVEL OF INDONESIAN - Wulandari, Putri Ayu; Fadilla, Annisa Rizky (Journal of Language, Literature and Teaching, 2023)
This research uses a type of literature review research. Literature review is an activity that involves analysis, evaluation and synthesis of library sources relevant to the research topic, which in this article discusses theories from journals, books and literature or other sources as material. studies that can later be applied in further research, so that the instruments used in this research are theories related to language theory at the linguistic level of Indonesian. The results obtained in this research can be used to analyze matters relating to Indonesian linguistics. The meaning of words has several types, namely lexical, grammatical, denotative, connotative, primary and secondary, figurative, literal, intentional, cognitive, constructional, contextual meaning. , broad, social, narrow, affective, stylistic, collocational, descriptive, conceptual and extensional. Meanwhile, relations and forms of meaning include; synonymy, antonymy, homonymy, polysemy, hyponymy, ambiguity and redundancy. The principles of meaning relationships include inclusion, overlap, complementarity, intersection.Keywords: literature review, linguistic, indonesian languange.